Chinese-Danish Relations: The Collapse of a Special Relationship - Kjeld Erik Brødsgaard (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2010)
Denmark was among the first countries in the world to recognize the People's Republic of China. The created a good foundation for the development of a special relationship between China and Denmark, culminating in Prime Minister, Poul Hartling's meeting with Mao in October 1974 and characterized by further intensification of political, economic and cultural relations from the beginning of the 1980s. The recent agreement to establish a joint Sino-Danish University Centre in Beijing constitutes yet another high point. However, there have also been incidents of tension and conflict. This paper will especially address three of these incidents: the "cartoon crisis" of August 1967, the Danish criticism of China's human rights record in the spring of 1997, and the controversy relating to the Dalai Lama's visit to Denmark in May 2009. It is argued that the costs of pursuing a policy towards China based on normative considerations have become too high and is difficult to harmonize with a new Danish foreign policy of active internationalism.
hdl:10398/8223
Keywords: 330; Internationale Beziehungen; Menschenrechte; China; Dänemark